Convergence to approximate solutions and perturbation resilience of iterative algorithms. (1st March 2017) - Reich, Simeon; Zaslavski, Alexander J
Abstract: We first consider nonexpansive self-mappings of a metric space and study the asymptotic behavior of their inexact orbits. We then apply our results to the analysis of iterative methods for finding approximate fixed points of nonexpansive mappings and approximate zeros of monotone operators.